2017
DOI: 10.1039/c7py00448f
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic diselenide crosslinkers to enhance the reprocessability and self-healing of polyurethane thermosets

Abstract: We explore the utilization of aromatic diselenides as new low temperature exchangeable monomers for their utilization in thermosets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 29 publications
1
80
0
Order By: Relevance
“…Besides, after the same healing process, the tensile strength and ultimate elongation of PTPU‐T restore to 29.3% and 24.5% of the original values, respectively, also both lower than that of A‐LP23‐T (61.2% and 29.7%). The healing efficiencies of PTPU‐I and PTPU‐T, without dynamic disulfide bonds, may be attributed to the contribution of the hydrogen bonds interaction . The higher healing efficiencies of A‐LP23‐I and A‐LP23‐T are inseparable from the effect of the disulfide metathesis reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, after the same healing process, the tensile strength and ultimate elongation of PTPU‐T restore to 29.3% and 24.5% of the original values, respectively, also both lower than that of A‐LP23‐T (61.2% and 29.7%). The healing efficiencies of PTPU‐I and PTPU‐T, without dynamic disulfide bonds, may be attributed to the contribution of the hydrogen bonds interaction . The higher healing efficiencies of A‐LP23‐I and A‐LP23‐T are inseparable from the effect of the disulfide metathesis reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with disulfide bonds, diselenide bonds are more dynamic due to a lower bond energy. Thereby, PU networks with aromatic diselenide exhibit the greater ability to be processed . What is more, Cheng's group reported that the hindered urea bonds showed a dynamic nature under ambient/catalyst‐free conditions .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, taking the reversible nature of dynamic covalent bond to fabricate self‐healing materials becomes the intriguing challenge of the scientists and engineers. Currently known self‐healing materials containing disulfide bonds are regarded as one of the most promising alternatives due to the reversible nature, high versatility, and low price . Although many significant results have been reported, some of these materials needed high temperatures and even external pressures to be healed and remolded .…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that diselenide bonds can be more dynamic, and their exchange reactions are probably occurred under much milder conditions. In fact, diselenide bonds have been incorporated into PU materials that can be self‐healed under light or heat . Ji et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation